Measuring Ecological Loss as State Loss in Illegal Mining Crime - Subekti, Prio Harry; Nabiatus Sa'adah (Unram Law Review, 2025)
The environment is one of the most important elements of life for human life whose rights are guaranteed following Article 28 H of the 1945 Republic of Indonesia Constitution. Therefore, the environment shall be maintained as an ecosystem from pollution and damaged. This research aim is to measure the ecological losses arising from illegal mining crimes as a state loss. This research is normative legal research that uses juridical analysis using a conceptual and a statutory approach. The study results found that ecological losses from illegal mining crimes can be calculated or used as state losses due to damage or loss of function of the environment due to illegal mining which is detrimental to society and the state. Therefore, incorporating ecological damage as a state loss may maintain human rights and environmental rights.